The Relationship of Plasma Fibrinogen, Erythrocyte Flexibility and Blood Viscosity - Dupont, P. A; Sirs, J. A (Thrombosis and Haemostasis, 1977)
Measurements have been made of plasma fibrinogen concentration, erythrocyte flexibility and blood viscosity at shear rates from 5.75 to 230 sec−1 during and following surgery. In the post-operative period the plasma fibrinogen level in the patient rose to over 1,000 mg/dl and because there were subsequent complications, only returned to normal after 4 weeks. There was an associated change of erythrocyte flexibility, with a correlation coefficient of 0.98. The blood viscosity also varied with the plasma fibrinogen level, the effect being more pronounced at low shear rates. The internal viscosity of the red blood cell, calculated from the plasma viscosity and whole blood viscosity at 230 sec−1, decreases with increasing plasma fibrinogen concentration, in agreement with the direct measurements made of erythrocyte flexibility. It is proposed that at high shear rates an increase in plasma viscosity due to an elevation of fibrinogen concentration, is offset by a decrease in the rigidity of the erythrocytes, and these 2 effects counter-balance.